Reimagining the Gendered Nation : Citizenship and Human Rights in Postcolonial Kenya - Kenny, Christina (Eastern Africa Series ;, 2022)
Explores the complex and intersecting dimensions of gender, ethnicity, and culture on women in the Global South, as well as the central roles of women in resisting colonial rule, and their foundational contributions to post-independence constitutional reform and nation building.